Reflectance confocal microscopy of tinea nigra: comparing images with dermoscopy and mycological examination results - John Verrinder Veasey; Ricardo Bertozzi de Avila; Marcus Antônio Maia de Olivas Ferreira; Rosana Lazzarini (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Tinea nigra is a superficial mycosis whose diagnosis is confirmed by isolating the infectious agent Hortae werneckii through mycological examinations. In vivo reflectance confocal microscopy, initially used in melanocytic dermatosis, has been used with skin infectious diseases to identify the parasite at the cellular level. We report, for the first time in the scientific literature, the use of reflectance confocal microscopy in a case of tinea nigra and compare its findings to dermoscopy and mycological examination results.